Rancang Bangun Pelaporan Penyalahgunaan Narkoba Badan Narkotika Nasional (BNN) Kota Kediri Berbasis Android - Lilik Nuryanto; Dwi Budi Santoso (Fakultas Teknik Universitas Hamzanwadi, 2022)
This study aims to observe, understand, design and build an information system for reporting drug abuse in the city of Kediri. This study uses the Waterfall method. The research subject is a system that can report drug abuse itself. The theoretical basis of the research used by the author uses Geographic Information Systems. GIS is a computer-based system that aims to store, manipulate, and analyze geographic information. In this research the author uses the Java programming language and the MYSQL database system as user data storage. Username using the primary key Employee Identification Number (NIP). For location mapping that has been carried out by the RPE Action, users who have created an account will be able to access the camera on a smartphone. Later the photos taken by the user will show the location of Latitude and Longitude. The research modeling uses DFD (Data Flow Diagram) modeling which contains DFD level 0 and level 1, ERD (Entity Realionship Diagram) and Flowchart. This study contains interface design, login interface design, main menu design, abuse reporting menu design, service menu design, socialization request menu design, rehabilitation request menu design, P4GN menu design, counseling request menu design, user menu design, mentoring menu design abuse, abuse report table design, edit profile menu design. Interface design is an important part of the application, because the first thing you see running is the application interface